Human monocyte-derived type 1 and 2 macrophages recognize Ara h 1, a major peanut allergen, by different mechanisms - Maren Krause (Nature Portfolio, 2021)
Abstract Evidence has suggested that major peanut allergen Ara h 1 activates dendritic cells (DCs) via interaction with DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin), a C-type lectin receptor, and contributes to development of peanut allergy. Since macrophages, as well as DCs, play a crucial role in innate immunity, we investigated whether natural Ara h 1 (nAra h 1) activates two different subsets of macrophages, human monocyte derived macrophage type 1 (hMDM1: pro-inflammatory model) and type 2 (hMDM2: anti-inflammatory model). hMDM1 and hMDM2 predominantly produced pro-inflammatory cytokines (IL-6 and TNF-α) and an anti-inflammatory cytokine (IL-10) in response to nAra h 1, respectively. hMDM2 took up nAra h 1 and expressed DC-SIGN at higher levels than hMDM1. However, small interfering RNA knockdown of DC-SIGN did not suppress nAra h 1 uptake and nAra h 1-mediated cytokine production in hMDM2. Inhibitors of scavenger receptor class A type I (SR-AI) suppressed the response of hMDM2, but not of hMDM1, suggesting that SR-AI is a major receptor in hMDM2 for nAra h 1 recognition and internalization. nAra h 1 appears to exert stimulatory capacity on DC and macrophages via different receptors. This study advances our understanding how a major peanut allergen interacts with innate immunity.